The effect of purine phosphonomethoxyalkyl derivatives on DNA synthesis in CHO Chinese hamster cells - Stĕtina, R; Votruba, I; Holý, A; Merta, A (Neoplasma, 1993)
The inhibition of incorporation of 3H-thymidine and the changes of the rate of nascent DNA chain elongation were investigated in CHO Chinese hamster cells treated with (S)-(3-hydroxy-2-phosphonomethoxypropyl) (HPMP) and N-(2-phosphonomethoxyethyl) (PME) derivatives of adenine (A), guanine (G) and 2,6-diaminopurine (DAP). No direct correlation was observed in PME and HPMP derivatives between cytotoxicity, inhibition of 3H-thymidine incorporation and inhibition of nascent DNA chain elongation. The highest cytotoxicity and inhibition of DNA synthesis were caused by PMEG. The limited extent of inhibition of DNA elongation was encountered in the case of HPMPG and HPMPA. With PMEA, weak inhibition of elongation of DNA was observed only after a prolonged exposure (6 h). None of the investigated drugs induced DNA breaks.
Keywords: poškození DNA; replikace DNA; CHO buňky; Dose-Response Relationship, Drug; Animals; DNA Replication; organofosfonáty; Guanine; Antiviral Agents; cytarabin; vztah mezi dávkou a účinkem léčiva; DNA Damage; Organophosphorus Compounds; Cricetulus; Zidovudine; Adenine; křečci praví; Organophosphonates; zidovudin; adenin; Cricetinae; antivirové látky; organofosforové sloučeniny; Cytarabine; CHO Cells; zvířata; guanin